Acupuncture improves the emotion domain and lipid profiles in women with polycystic ovarian syndrome: a secondary analysis of a randomized clinical trial - Chang, Hui; Shi, Baichao; Ge, Hang; Liu, Chengdong; Wang, Lirong; Ma, Chengcheng; Liu, Lifeng; Zhang, Wanyu; Zhang, Duojia; Wang, Yong; Wang, Chi Chiu; Wu, Xiaoke (Frontiers in Endocrinology, 2023)
This study aims to evaluate the effect of acupuncture on emotion domain and metabolic parameters of Chinese women with polycystic ovarian syndrome (PCOS) by secondary analysis of a randomized clinical trial, conducted from July 6, 2012 to October 7, 2015.In this study, we investigated the effects of acupuncture (458 patients) and sham acupuncture (468 patients) on metabolic parameters, serum ions and all quality of life scale scores related to PCOS. The quality of life of patients were evaluated using 5 relevant scales, operated by the research assistant, including PCOSQ, SF-36 and ChiQOL, as well as Zung-SAS and Zung-SDS. Metabolic parameters and serum ions were measured.A reduction in acne score, AN, Hcy and LDL-C, and increase in lever of lipoprotein α, Apo A1, Apo A1/Apo B were observed in acupuncture group after 4 months intervention after adjusting clomiphene and reproductive outcome (P<0.05). A increase in SF-36 total scores, RP and RE scores, ChiQOL total scores and emotion domain scores were observed in acupuncture group after 4 months intervention, while PF and HT scores were decreased (adjusted P<0.05). Similar changes were observed in sham acupuncture group. Meanwhile, the serum levels of Ca, K and Cl were elevated in acupuncture group after the interventions (adjusted P<0.005). There were no significant differences in HOMA-IR, MetS, FPG, FINS, HDL-C, TG, Apo B and lever of serum P, Mg and Na. Also, no changes in BP, GH, VT, SF, physical form domain and spirit domain were observed after treatment.Acupuncture not only can improve the emotional changes in SF-36 scores and ChiQOL scores, but also can improve lipid metabolism, implying that may have a correlation between emotional changes and lipid metabolism. Furthermore, acupuncture also can regulate the changes of serum Ca, K and Cl.